PHYTOCHEMICAL CONSTITUENTS AND ANTIFUNGAL ACTIVITY OF ACALYPHA WILKESIANA LEAVES ON CANDIDA ALBICANS - Sulaiman, Asmau Nna; James, Adole Emmanuel (FUDMA JOURNAL OF SCIENCES, 2023)
Acalypha wilkesiana, commonly called Jacob’s coat, is native to South Pacific Islands and belongs to the family Euphorbiaceae. This study was conducted to evaluate the phytochemical constituent and the antifungal effect of methanolic and aqueous extracts of Acalypha wilkesiana leaves on Candida albicans. The aqueous and methanolic extracts of Acalypha wilkesiana were investigated for their antifungal activity against Candida albicans using agar well diffusion method. A total of twenty (20) isolates were collected from Ahmadu Bello University Medical Centre, Samara, Zaria, of which all were confirmed using microscopy (wet mount), culture and Germ tube test to be Candida albicans. The plant extract was prepared using maceration method. The preliminary phytochemical screening of the extract showed the presence of alkaloids, cardiac glycosides, saponins, phenolic compounds, tannins, steroids, carbohydrates, flavonoids and terpenoids. The Minimum Inhibitory Concentration for both the aqueous and methanolic extracts were at 100 mg/mL and 75 mg/mL. The Minimum Fungicidal Concentration for both extracts were at 100 mg/mL. Acalypha wilkesiana studied here can be seen as a potential source of useful drugs. The result of this study therefore justifies the use of plant as the herbal medicine for the treatment of fungal infection caused by Candida albicans.
Keywords: Alcalypha wilkesiana; Candida albicans; Candidiasis; fungal infection; vagina